Diseño de una metodología gráfica para el diagnóstico del mecanismo de producción de agua en pozos petroleros verticales y desviados para futuros trabajos de control de la misma en fondo (2020)
The exploitation of oil fields which produce heavy and/or mature crude represents a challenge for the oil industry because they have to handle large volumes of water associated with production, increasing the lifting cost and affecting most of the field operations. The maintenance of water in the reservoir involves making a diagnosis that identifies whether the mechanism of water production is coning, multilayer channeling, flow behind casing or even a combination of these. Today, there are methodologies to identify such mechanisms such as the Chan curves and the Ramos method; however, these present several limitations and/or shortcomings increasing the uncertainty in the diagnosis.